PENGARUH PEMBELAJARAN TPS TERHADAP HASIL BELAJAR DITINJAU DARI KETERAMPILAN BERKOMUNIKASI - Citra Wuri Handayani (Universitas Sarjanawiyata Tamansiswa, 2017)
The objective of this study descriptively is to know the result of Science’s learning achievement from communication skill and comparatively to know the differences of learning achievement of Science subject between the teaching that uses TPS Model and Conventional Learning Model. The type of this research is a quasi-experiment. The data collection techniques use documentation, questionnaire, and test. Data analysis technique uses a descriptive analysis and Anacova. Descriptively, the result of the research shows that learning achievement used TPS was very high criteria and Conventional Model was in high criteria. The communication skill that used TPS was high criteria and Conventional Model was in high criteria. Comparatively, there was an influence of the use of TPS Model toward the learning achievement of science subject from communication skill.